2020
DOI: 10.3389/fphys.2020.576736
|View full text |Cite
|
Sign up to set email alerts
|

RNase A Treatment Interferes With Leukocyte Recruitment, Neutrophil Extracellular Trap Formation, and Angiogenesis in Ischemic Muscle Tissue

Abstract: Background: RNase A (the bovine equivalent to human RNase 1) and RNase 5 (angiogenin) are two closely related ribonucleases. RNase 5 is described as a powerful angiogenic factor. Whether RNase A shares the same angiogenic characteristic, or interferes with vessel growth as demonstrated for arteriogenesis, has never been investigated and is the topic of this present study. Methods and Results: To investigate whether RNase A shows a pro-or anti-angiogenic effect, we employed a murine hindlimb model, in which fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 76 publications
(122 reference statements)
1
6
0
Order By: Relevance
“…Though the direct evidence of NETs in angiogenesis and vascular permeability in the context of tumor is scarce, a functional link between NETs and angiogenesis has been implicated in tissue repair [ 63 ] as well as in vascular pathology, including pulmonary hypertension [ 64 ] and corneal neovascularization [ 65 ]. The possible mechanism could be NETs-mediated activation of endothelial cells via TLR-4/ NFκB signalling [ 64 ], inflammation-induced upregulation of proangiogenic factors such as vascular endothelial growth factor (VEGF) [ 65 , 66 ] , and the newly identified mechanism relying on the NETs clearance of senescent endothelial cells [ 67 ]. In addition to angiogenesis, NETs have been found to increase vascular permeability by disrupting the endothelial barrier.…”
Section: Nets Promote Metastasismentioning
confidence: 99%
“…Though the direct evidence of NETs in angiogenesis and vascular permeability in the context of tumor is scarce, a functional link between NETs and angiogenesis has been implicated in tissue repair [ 63 ] as well as in vascular pathology, including pulmonary hypertension [ 64 ] and corneal neovascularization [ 65 ]. The possible mechanism could be NETs-mediated activation of endothelial cells via TLR-4/ NFκB signalling [ 64 ], inflammation-induced upregulation of proangiogenic factors such as vascular endothelial growth factor (VEGF) [ 65 , 66 ] , and the newly identified mechanism relying on the NETs clearance of senescent endothelial cells [ 67 ]. In addition to angiogenesis, NETs have been found to increase vascular permeability by disrupting the endothelial barrier.…”
Section: Nets Promote Metastasismentioning
confidence: 99%
“…Moreover, while a direct inhibition of NETs via DNase has been postulated as a potential mechanistic treatment strategy to reduce NET burden ( Ondracek et al, 2020 ; Korai et al, 2021 ), there is mounting evidence that NET-associated RNA is a relevant component of NET formation and can occur independently of DNA ( Herster et al, 2020 ). Based on this finding and previously published data on the dampening effects of RNase A on immune cells ( Lasch et al, 2020 ), we questioned whether RNase A also modifies NET formation. Indeed, our data show that RNase A significantly reduces NET formation in all compartments of the brain.…”
Section: Discussionmentioning
confidence: 80%
“…Next to extracellular DNA, other alarmins or so-called danger-associated molecular pattern (DAMP) signals such as extracellular RNA (exRNA) have been described as a key player in the involvement of central system pathologies, including hemorrhagic stroke ( Tielking et al, 2019 ). In this context, RNase is a natural enzyme involved in the regulation of vascular homeostasis that can counteract exRNA when applied exogenously ( Fischer et al, 2011 ; Lasch et al, 2020 ; Preissner et al, 2020 ). Recent studies have shown that NET-associated RNA is a relevant NET component and its formation can occur also independently of DNA, which opened the hypothetical avenue that RNase A (the bovine equivalent to human RNAse1) may also modify NET formation in vivo SAH models ( Herster et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The different steps of leukocyte recruitment appear to be a blueprint for arteriogenesis taken from the respective steps in innate immunity, whereby exRNA is considered in this context not to be a damaging component but rather a vessel and tissue regenerating factor. Although the aforementioned process of collateral artery growth also entails reactions of vasculogenesis and angiogenesis at distant sites, a definitive role of exRNA here is still speculative (Lasch et al, 2020). Nevertheless, in an ex vivo cellular spheroid model of vasculogenesis, exRNA was found to stimulate the formation of new vessels and leukocyte differentiation in embryonic bodies via increased VEGF-dependent signaling and ROS production (Sharifpanah et al, 2015).…”
Section: Exrna and Arteriogenesis: A Blueprint For The Creation Of Namentioning
confidence: 99%